Classification of Property and Conceptions of Ownership in Civil and Common Law - Pierre, Barbara (Revue générale de droit, 1997)
This paper examines the classification of property in common law and civil law, by contrasting the conceptions of ownership in each tradition. The author aims to provide a comparative analysis of the fundamental concepts and institutions of the law of property in each tradition. This is deemed useful, not only for promoting a better understanding of the law of property by jurists in both traditions, but also for enabling the jurist of one tradition, to find his way in the unfamiliar territory of the other tradition.The author demonstrates that ownership in common law—insofar as it exists—is constructed on the ruins of the feudal system. Having been developed in an ad hoc manner from such origins, the law of property is seen to be an amalgam of technical and complex principles, built around institutions which sometimes have archaic features that serve no useful purpose in the present day. The theory of "estates", which is espoused, is however acclaimed for its flexibility, its most celebrated attribute being that invaluable institution, the Trust.Ownership in civil law in contrast, is shown to have developed from the romanisation of the feudal system. The law of property, its principles and institutions, are more systematically and rationally organised. They are therefore more easily assimilated and applied. The theory of absolute ownership which is at its core, is however criticised for being, to some extent, inflexible.Using this historical and conceptual background, the author shows that underneath the façade of similar powers over land in the two traditions, lies fundamental juridical differences in the nature and characteristics of the institutions—even those bearing the sames names.